Harnessing Biogenic Silica: Nanoarchitected Pt3Pd1 on Nettle-Derived N,Si-CQDs for High-Performance Methanol Electrooxidation - Beyhan, Seden (MDPI AG, 2025)
This study introduces nitrogen- and silicon-containing carbon quantum dots (N,Si-CQDs), synthesized hydrothermally from the sustainable bioresource stinging nettle (Urtica dioica L.), as chemically active supports for Pt, Pd, and Pt3Pd1 electrocatalysts. The N,Si-CQDs were characterized by a high concentration of N/O surface functionalities and the presence of biogenic Si. A significant finding is that, with this support, biogenic Si acts as a nucleation template: Pd forms in situ as orthorhombic Pd9Si2 nanorods alongside spherical particles, whereas Pt predominantly develops as cubic/quasi-cubic crystals. This templating process promotes faceted (cubic) Pt3Pd1 alloy nanoparticles with robust interfacial contact with the support and a log-normal size distribution (14.2 ± 4.3 nm) on N,Si-CQDs (4.7 ± 1.4 nm). This configuration enhanced the electrochemically active surface area to 181 m2 gPt−1, significantly exceeding those of commercial Pt1Pd1/XC-72 (27.7 m2 gPt−1) and monometallic Pt/N,Si-CQDs (14.3 m2 gPt−1). Consequently, the catalyst demonstrated superior methanol oxidation performance, evidenced by a low onset potential (0.17 V), approximately 10-fold higher mass activity compared to Pt1Pd1/XC-72, and 53% activity retention after a 16 h accelerated durability test. The enhanced performance is attributed to the strong nanoparticle anchoring by N,Si-CQDs, the bifunctional/ligand effects of the Pt–Pd alloy that improve CO tolerance, and the templating role of biogenic Si.
Keywords: Article